Mga piling diskurso sa wika at lipunan - 4 0 16; Constantino, Pamela C.; 5 (Diliman, Lunsod Quezon : University of the Philippines Press, 1996)
Influence of Filipino language on Philippines society.
In Tagalog.
Keywords: 2 -- 0; 6; Social aspects. -- Tagalog language;Language and culture;Languages in contact -- Philippines;Philippines.;Philippines. -- 20; 20; 2